Cobalt concentration in a sulfidic sea and mobilization during orogenesis: Implications for targeting epigenetic sediment-hosted Cu-Co deposits. (15th July 2021) - Qiu, Zheng-Jie; Fan, Hong-Rui; Goldfarb, Richard; Tomkins, Andrew G.; Yang, Kui-Feng; Li, Xiao-Chun; Xie, Lie-Wen; Liu, Xuan
Highlights: Oxidative weathering and evaporative settings favor accumulation of Co-rich sedimentary pyrite in a sulfidic ocean. Cobalt is released and mobilized during orogenic deformation and metamorphism. Pyrite recrystallization causes cobalt release and minor S-Fe isotope variations. Globally, evaporative marine sequences formed at ca. 2.2–2.0 and 0.9–0.7 Ga are the ideal target areas for Co resources, including those hosted in orogenic belts. Abstract: The origin of sediment-hosted copper-cobalt deposits (SCDs) within metamorphic terranes remains contentious, particularly in regard to the timing of mineralization relative to basin evolution. Here, we link the timing of Cu-Co mineralization in the Zhongtiao Mountains district, central China, to basin closure during development of the Trans-North China Orogen. Metamorphic apatite from meta-evaporite has a U-Pb age (1844 ± 25 Ma) within error of a Re-Os age for molybdenite from Cu- and Co-bearing veins (1819 ± 10 Ma), implying that mineralization and metamorphism were coincident. In situ trace element and Fe-S isotope analyses of deformed sedimentary pyrite (Py I) and younger euhedral metamorphic pyrite (Py II) in pyritic graphite schist indicate that Co was mobilized from Py I via fluid-mediated dissolution and reprecipitation. In the graphite schist, representing a sulfidic shale metamorphosed at upper greenschist facies conditions, relic Py I has high δ 34 S values (22.9 ± 0.4‰, n = 10) and δ 56 Fe values (0.90 ± 0.16‰, n = 8). These values are consistent with bacterial sulfate reduction and pyrite formation in a Paleoproterozoic sulfidic sea (i.e., after the first great oxygenation event). In addition, Py I has unusually high Co contents (0.8–3.0 wt.%), suggesting that transition metals, including Co and Ni, were originally concentrated in sedimentary pyrite in an evaporative setting. The evaporitic setting is supported by the presence of sylvite in sulfidic schists and adjacent scapolitic calc-silicates. Younger Co-poor Py II has slightly lower δ 34 S values (21.4 ± 0.2‰, n = 19) and higher δ 56 Fe values (1.61 ± 0.15‰, n = 9), supporting the hypothesis that Co was released from sedimentary sulfide during dissolution and reprecipitation. The great variability of δ 34 S (14.8 to 22.9‰) and δ 56 Fe (0.13 to 2.30‰) in hydrothermal pyrite (Py III) associated with Cu-Co mineralization suggests that an external Cu-rich oxidizing fluid was involved in the ore-forming process. Copper and Co in this type of deposit are typically both considered to be derived from fertile basement rocks. This study, however, highlights another potential source for the Co, with its enrichment in a sulfidic sea along an evaporative margin and its upgrading through mobilization during orogenesis that leads to formation of a relatively high-temperature group of SCDs. Tectonometamorphic processes causing such Co enrichments took place during the Paleoproterozoic and Neoproterozoic oxygenation events, implying that the most prospective targets for Co resources are concentrated in ca. 2.2–2.0 Ga and 0.9–0.7 Ga deformed passive margin marine sequences.